ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT PADA BANK PEMERINTAH DI INDONESIA - Roswita AB; Enny Muhaini Hanafiah; Darmawan Rachmad (Jurnal Ekonomi Pembangunan, 2003)
The disturbance of banking intermediation or more popular in term disintermediation of credit distribution is reflected by the low position of LDR national banking. The low position of LDR indicates the decrease of banking ability in distributing credit if it is compared to the banking ability in collecting fund from society. For analyzing this problem, the used multiple regression linear method. The result of regression research indicated that for the period of 1991- 2001, Â credit distribution is significantly affected by the number of bank offices variable andÂ inflation level. As the contrary, the variable of society fund, credit interest, minimum reserve, and exchange rate do not significantly influence toward credit distribution variable for the period 1991-2001.